Madam Pasey’s Farewell at IBEC - Cindy, Peter (IBEC, 2020)
On 28 February 2020, a farewell luncheon was organized for Madam Pasey Lisus, IBEC’s Office Secretary. It was attended by the Director, Assoc. Prof. Dr. Mohd Azlan Jayasilan, all IBEC Research Fellows, and postgraduate students. Madam Pasey had been working in UNIMAS since 2001, and was in IBEC from February 2015. Prior to that, she was at the Centre for Applied Learning and Multimedia (CALM).